Kinesthetic intelligence and its relationship to the performance of some fixed cases for the players of the Sugar Sports Club in football - Assistant Lecturer. Hassanein Sharif AbdelWahab (Zien Journals, 2023)
Undoubtedly, we are now living in a different era by all standards than in past eras, and this means that the power of truth now is for those who possess information and can use it optimally. The current time is characterized by the need for intelligence, especially in the sports field. There is no doubt that intelligence comes at the forefront of the psychological aspects and mental abilities that must be given great care in relation to the athlete, especially in team games, as it has great repercussions from the athlete who is related to education programs, training curriculum and relations between players. Intelligence (One of the important variables in learning sports motor skills, especially collective games, which requires focus and quick awareness of the different relationships that are required by the nature of the situations to play during the match). Where football is one of the games that are characterized by suspense and fun and provide an integrated educational environment such as cooperation and teamwork Respect for laws and competition, and in order for countries to advance in the field of football, their interest was focused on preparing a strong base of practitioners of the game at an early age, in order to ensure that they reach higher levels. Despite all the developments provided by countries and clubs to coaches and players, through which many variables and expected influences can be controlled, the psychological aspect remains one of the aspects that cannot be tightly controlled and refined in an integrated manner for the purpose of steadfastness in the face of circumstances. Many professional players faced situations in which they failed and the evidence is Accordingly, the penalty kicks in which the players' experience failed, and this is due to psychological conditions and reasons that may include lack of awareness or intelligence of the players
Keywords: Kinesthetic intelligence; Sugar Club; Football; Measures of physical intelligence